The fragility and reliability of conclusions of anesthesia and critical care randomized trials with statistically significant findings: A systematic review - Grolleau, F; Collins, G; Smarandache, A; Pirracchio, R; Gakuba, C; Boutron, I; Busse, J; Devereaux, P; Le Manach, Y (Lippincott, Williams & Wilkins, 2018)
Objectives: The Fragility Index, which represents the number of patients responsible for a statistically significant finding, has been suggested as an aid for interpreting the robustness of results from clinical trials. A small Fragility Index indicates that the statistical significance of a trial depends on only a few events. Our objectives were to calculate the Fragility Index of statistically significant results from randomized controlled trials of anesthesia and critical care interventions and to determine the frequency of distorted presentation of results or “spin”. Data Sources: We systematically searched MEDLINE from January 01, 2007, to February 22, 2017, to identify randomized controlled trials exploring the effect of critical care medicine or anesthesia interventions. Study Selection: Studies were included if they randomized patients 1:1 into two parallel arms and reported at least one statistically significant (p ≺ 0.05) binary outcome (primary or secondary). Data Extraction: Two reviewers independently assessed eligibility and extracted data. The Fragility Index was determined for the chosen outcome. We assessed the level of spin in negative trials and the presence of recommendations for clinical practice in positive trials. Data Synthesis: We identified 166 eligible randomized controlled trials with a median sample size of 207 patients (interquartile range, 109–497). The median Fragility Index was 3 (interquartile range, 1–7), which means that adding three events to one of the trials treatment arms eliminated its statistical significance. High spin was identified in 42% (n = 30) of negative randomized controlled trials, whereas 21% (n = 20) of positive randomized controlled trials provided recommendations. Lower levels of spin and recommendations were associated with publication in journals with high impact factors (p ≺ 0.001 for both). Conclusions: Statistically significant results in anesthesia and critical care randomized controlled trials are often fragile, and study conclusions are frequently affected by spin. Routine calculation of the Fragility Index in medical literature may allow for better understanding of trials and therefore enhance the quality of reporting.